2016
DOI: 10.1371/journal.pone.0152853
|View full text |Cite
|
Sign up to set email alerts
|

Virulent Mycobacterium bovis Beijing Strain Activates the NLRP7 Inflammasome in THP-1 Macrophages

Abstract: Mycobacterium bovis is the causative agent of tuberculosis in a wide range of mammals, including humans. Macrophages are the first line of host defense. They secrete proinflammatory cytokines, such as interleukin-1 beta (IL-1β), in response to mycobacterial infection, but the underlying mechanisms by which human macrophages are activated and release IL-1β following M. bovis infection are poorly understood. Here we show that the ‘nucleotide binding and oligomerization of domain-like receptor (NLR) family pyrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…The protein level of AIM2, the cytoplasmic sensor molecule, was elevated over time after infection of THP-1 cells despite the fact that AIM2 mRNA increased only at 6 hours post EBV incubation and subsequently decreased. Sustainment of the protein level of PRRs after peak expression of their mRNAs was also observed in another study [26]. Furthermore, the AIM2 mRNA level was significantly increased in primary human monocytes after EBV infection.…”
Section: Discussionsupporting
confidence: 71%
“…The protein level of AIM2, the cytoplasmic sensor molecule, was elevated over time after infection of THP-1 cells despite the fact that AIM2 mRNA increased only at 6 hours post EBV incubation and subsequently decreased. Sustainment of the protein level of PRRs after peak expression of their mRNAs was also observed in another study [26]. Furthermore, the AIM2 mRNA level was significantly increased in primary human monocytes after EBV infection.…”
Section: Discussionsupporting
confidence: 71%
“…We also found residual caspase-1-dependent IL-1β maturation in cells lacking NLRP3 and AIM2, pointing towards the involvement of other inflammasome sensors. A recent study identified the NLRP7 inflammasome as a mediator of caspase-1 activation during Mycobacterium bovis infection 49 . Microbial lipopeptides signalling via TLR2 have also been shown to activate the NLRP7 inflammasome 50 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β has been found to play an important role in the anti-mycobacterial response by aiding in macrophage destruction of mycobacteria [58, 59]; however, its expression by γδ T cells has not been previously characterized during M. bovis infection. One caveat to our transcriptomics analysis is the approach used to prepare our γδ T cells.…”
Section: Discussionmentioning
confidence: 99%